A New Parameterized Monogamy Relation between Entanglement and Equality. Issue 6 (28th March 2022) - Jin, Zhi‐Xiang; Fei, Shao‐Ming; Li‐Jost, Xianqing; Qiao, Cong‐Feng
Abstract: A generalized definition of the monogamy relation for entanglement measures is provided. A monogamy equality rather than the usual inequality is presented based on the monogamy weight, from which monogamy relations are given satisfied by the αth ( α > 0 ) $(α >0)$ power of the entanglement measures. Taking concurrence as an example, the significance and advantages of these relations are further demonstrated. In addition, it is shown that monogamy relations can be recovered by considering multiple copies of states for every non‐additive entanglement measure that violates the inequalities. It is also demonstrated that such relations for tripartite states can be generalized to multipartite systems. Abstract : In this article, a new parameterized monogamy relation between entanglement and equality is presented. It gives an operational interpretation of the ability to be monogamous for entanglement measure. Monogamy relations can be recovered by considering multiple copies of states for every non‐additive entanglement measure that violates the conventional inequalities. Monogamy equality for multipartite systems is also discussed.